Perceived benefits and church participation. Issue 5 (4th November 2014) - Casidy, Riza; Casidy, Riza; Tsarenko, Yelena
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to examine the relationship between perceived benefits and church participation among regular and irregular church goers (ICG). Design/methodology/approach – The research incorporates a descriptive research design. In total, 564 questionnaires were completed by active and relapsed members of churches in Australia. Hierarchical regression analysis was conducted to examine the relationship between constructs. Findings – This study provides empirical evidence that perceived spiritual and social benefits have a positive and significant relationship with church participation in both regular and ICG sample group. Perceived purpose-in-life (PIL) benefits are not related to church participation in both sample groups. Practical implications – The findings may guide leaders of religious organisations to understand the importance of spiritual and social benefits in attracting prospective church members. The marketing message of religious organisation should therefore focus on spiritual and social appeals. Originality/value – Past researchers have not looked into the dynamic relationships between perceived benefits and church participation among regular and irregular church members, particularly in Australia, hence research is to be called for in this area. The study provides a further empirical support for the importance of social benefits within the church settings.